Antioxidant enzyme activities and malondialdehyde levels in patients with obsessive-compulsive disorder - Kuloglu, M; Atmaca, M; Tezcan, E; Gecici, Ö; Tunckol, H; Ustundag, B (Karger, 2002)
To examine the importance of free radicals in the pathogenesis of obsessive-compulsive disorder (OCD), we aimed to evaluate whether malondialdehyde (MDA), a product of lipid peroxidation, and antioxidant enzyme [superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT)] activity levels were associated with OCD. The patients were divided into two subgroups according to whether DSM-IV major depressive disorder (MDD) was accompanied (OCD + MDD) or not (OCD - MDD). The MDA and antioxidant enzyme levels both in patients and controls were determined. SOD activity levels were significantly higher in the OCD + MDD group compared with the control and the OCD MDD group. Although the OCD - MDD group had slightly higher SOD activity levels as compared with the controls, the difference was not statistically significant. GSH-Px activity levels were statistically significantly higher in both groups compared with controls. Likewise, there was a significant difference in GSH-Px activity levels between the OCD + MDD and OCD - MDD group. CAT activity levels were slightly higher in the OCD + MDD group compared with the OCD - MDD and control group. MDA levels in both groups were significantly higher than in controls. In addition, the difference in MDA levels between both groups was statistically significant. In conclusion, our results suggest that OCD is associated with free radicals and that it may be a heterogeneous subtype including some biological indications of anxiety and affective disorders. More comprehensive and detailed studies are needed to decipher the exact role of free radicals in OCD. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: obsessive-compulsive disorder; antioxidant enzyme activities; malondialdehyde